Lecturer's Experience of Guiding Students Facing Exit Exam as A Requirement to Get A Ners Degree - Simamora, Febrina Angraini; Daulay, Nanda Masraini; Sagala, Nanda Suryani; Siregar, Hotma Royani (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2022)
Introduction: The exit exam is a competency test that is carried out at the final stage after completing all stages of education which is part of the assessment of student learning outcomes in the health sector. The aim of this study was to explore in depth the experience of lecturers guiding students to face the exit exam as a condition for obtaining a nursing degree.Method: The study used a phenomenological design. Five participants were selected by purposive sampling with criteria inclusion. Result: The data were gathered by conducting in-depth interviews and analyzed by Collaizi method. The result emerged four themes, namely: 1) Response to application of exit exam; 2) Facilitating students in facing the exit exam; 3) Obstacles in guiding students; 4) Lecturers' expectations of the Association of Indonesian Nurses Education Institutions.Conclusion: It is recommended for clinical supervisors to provide intensive guidance to nursing students so that they can prepare themselves to take the exit exam.